The importance of isometric maximum strength in college wrestlers - McGuigan, M. R.; Winchester, J. B.; Erickson, T. (Journal of Sports Science & Medicine, 2006)
Previous research has demonstrated the importance of isometric maximal strength (PF) and rate of force development (RFD) in a variety of athletic populations including track cyclists and track and field athletes. Among coaches and sports scientists there is a lack of agreement regarding how much strength is required for optimal performance in most sports. The purpose of this study was to examine relationships between measures of PF, RFD and one repetition maximum (1RM) strength with other variables that might contribute to successful performance in collegiate wrestlers. Eight men (M = 20.0, SD = 0.4 years; Height M = 1.68, SD = 0.13 m; Mass M = 78.0, SD = 4.2 kg) who were Division III college wrestlers participated in this study. They were tested for PF using the isometric mid thigh pull exercise. Explosive strength was measured as RFD from the isometric force-time curve. The 1RM for the squat, bench press and power clean exercises were determined as a measure of dynamic strength. Vertical jump height was measured to determine explosive muscular power. The wrestlers also ranked themselves and the coaches of the team also provided a ranking of the athletes. Correlations between the variables were calculated using the Pearson product moment method. Results indicated strong correlations between measures of PF and 1RM (r = 0.73 - 0.97). The correlations were very strong between the power clean 1RM and PF (r = 0.97) and squat 1RM and PF (r = 0.96). There were no other significant correlations with other variables apart from a strong correlation between RFD and coaches ranking (r = 0.62). Findings suggest that isometric mid thigh pull test does correlate well with 1RM testing in college wrestlers. RFD does not appear to be as important in college wrestlers. The isometric mid thigh pull provides a quick and efficient method for assessing isometric strength in athletes. This measure also provides a strong indication of dynamic performance in this population. The lack of strong correlations with other performance variables may be a result of the unique metabolic demands of wrestling.